Plan de negocios para la exportación a Quito-Ecuador de tratamiento capilar de la empresa Grace Angelique (2019)
The objective of this present work is to demonstrate the technical and financial viability of a hair treatment export project based on natural extracts to the city of Quito - Ecuador from Bogotá, by the company Grace Angelique. Feasibility studies are carried out in order to see the advantages, disadvantages, risks, investments, among others to achieve decision-making in this case of expansion through an export.